Adopting Mobile Money: Evidence from an Experiment in Rural Africa - Catia Batista; Pedro C. Vicente (Institute of Labor Economics (IZA), 2020)
Who uses mobile money? What is mobile money used for? This paper describes the mobile money adoption patterns following the experimental introduction of mobile money for the first time in rural areas of Southern Mozambique. We use a combination of administrative and household survey data to characterize early and late adopters, as well as their mobile money usage patterns during the three years after mobile money was introduced. We find that a large proportion of the individuals who were offered mobile money services actively adopted this technology. Adopters of mobile money (and early adopters in particular) are more educated than non-adopters, and they are also more likely to already hold a bank account. Positive self-selection of mobile money adopters raises questions about the effectiveness of mobile money as a tool for financial inclusion.
Keywords: O16; O33; G20; 330; financial deepening; financial inclusion; self-selection; technology adoption; mobile money; fintech; Mozambique; Africa